The effect of digital detox through digital minimalism using the MinimalistPhone app on the behavior of young users and their emotional experience - Milica Schraggeová; Daniel Bisaha (Computers in Human Behavior Reports)
The use of smartphones occupies a significant portion of daily work and non-work activities. Digital optimization, or digital detox, has emerged in research and popular literature as a potential solution to intensive smartphone use. This study evaluates the effectiveness of a digital detox intervention using the MinimalistPhone app. The theoretical framework includes dual user attitudes (implicit and explicit), process and social usage, habitual behavior formation and affective evaluation of smartphone use. A pretest-posttest design was employed with an experimental group (N = 29; mean age = 22.8 years; SD = 5.01) and a control group (N = 28; mean age = 25 years; SD = 8.08). Participants in the experimental group used the MinimalistPhone app for 14 days. The app encourages intentional smartphone use by disrupting habits and removing visual cues that trigger unconscious behavior. It increases cognitive effort with additional steps, such as searching an alphabetical list and tracking usage time, making it less intuitive for icon-reliant users. By prioritizing control over convenience, it fosters deliberate smartphone interaction. Data were collected on habitual, process, and social smartphone usage, affective states (via PANAS), and objectively measured screen time before and after the intervention. Results showed that the MinimalistPhone app reduced habitual behavior and overall screen time. However, findings should be interpreted cautiously, as pretest differences between groups were notable. The intervention did not significantly affect affective states. This study underscores the importance of further exploring explicit and implicit attitudes toward smartphone use to better understand and mitigate excessive use.